A New Evaluation of the Role of Urbanization to Warming at Various Spatial Scales: Evidence From the Guangdong‐Hong Kong‐Macau Region, China. Issue 20 (14th October 2020) - Chao, Liya; Huang, Boyin; Yuanjian, Yang; Jones, Phil; Cheng, Jiayi; Yang, Yang; Li, Qingxiang
Abstract: The urbanization impacts on surface air temperature (SAT) change in the Guangdong‐Hong Kong‐Macau region (GHMR) from 1979 to 2018 are examined using homogeneous surface observations, reanalysis, and remote sensing. Results show that the warming due to urbanization tends to be smaller or insignificant as the spatial scale increases. The urbanization contribution to the local warming can reach as high as 50% in the center of each metropolis, remains high (~25%) in the Greater Bay Area (GBA), and decreases to about 10% in the whole GHMR. The warming in GHMR is nearly uniform throughout the day, and therefore, the observed trend of the diurnal temperature range (DTR) is not statistically significant. However, the urbanization contribution exhibits distinct seasonal variations, large in summer and autumn while smaller in winter and spring. Plain Language Summary: The Guangdong‐Hong Kong‐Macau region (GHMR), especially the Greater Bay Area (GBA), is a region typical of China's economic development and rapid urbanization. To precisely assess how much the urbanization contributes to the regional warming, we comprehensively evaluate the urbanization warming and its uncertainties in GHMR by using more careful processed and assessed data (observations, reanalysis, and remote sensing) and different analysis methods. The results show that the warming due to urbanization tends to be smaller as the spatial scale increases: The contribution to the local warming can reach as high as 50% in the metropolis, remains high (~25%) in GBA, and decreases to about 10% in GHMR. In addition, this paper systematically discusses the uncertainty in urbanization contribution detection, which was often neglected in the past detection. Based on the significance tests, urbanization warming is nearly uniform throughout the day, while it exhibits distinct seasonal variation. Our study also has important implications for understanding the influences of human activities on regional climate change for other regions experiencing rapid urbanization processes. Key Points: The contribution of urbanization to regional warming is robust in homogenized SAT data and ERA5 reanalysis using different methods The spatial scale dependence of urbanization warming is investigated; the contribution of urbanization warming decreases when the scale increases Urbanization contribution exhibits distinct seasonal variation based on the uncertainty assessment